Measuring and evaluating socio-economic inequality in small areas: An application to the urban units of the Municipality of Genoa. (October 2022) - Alaimo, Leonardo Salvatore; Ivaldi, Enrico; Landi, Stefano; Maggino, Filomena
Abstract: Inverse relationship between socio-economic status and health has been widely investigated in literature. Focusing on the concept of deprivation, different empirical studies proved the existence of a relationship between it and health conditions, both at individual and territorial level. In this work we propose the application of a non-aggregative methodology, the Partially Ordered Set (poset), for the measurement of deprivation in small areas. In particular, the application considers the Urban Units of the Municipality of Genoa (Italy) and two different systems of indicators, one to measure material deprivation and the other for social deprivation. For each multi-indicators system, three synthetic measures were constructed that provide different information on the units considered: their position in the general order (average height), the ambiguity of their deprivation with respect to a given threshold (identification function) and the intensity of this deprivation (severity function). The results show that material deprivation is associated with higher mortality while social deprivation is not. We believe that the paper can be of twofold use. On the one hand, the application itself is interesting, providing an analysis of deprivation in small areas of the territory of Genoa. On the other hand, it is a useful contribution for policy analysis, presenting a method and the various steps to apply it. Highlights: Synthetic measures identifying accurately deprivation levels are an essential tool for policy makers to optimize allocation of resources. Health institutions ability to focus their interventions in the right geographical area can maximise health benefits for the society. The study analyzes levels of deprivation in Urban Units of the Municipality of Genoa, confirming the existence of a relationship between material deprivation and health conditions. The methodology proposed, poset, is particularly suitable for analysis and provides an informative patrimony on the phenomenon. Poset is an useful tool for the proper design of deprivation intervention policies.